Pulmonary haemosiderosis and gluten. Issue 5 (May 1987) - Reading, R; Watson, J G; Platt, J W; Bird, A G
Abstract : A child with idiopathic pulmonary haemosiderosis for three years required three monthly transfusions. Circulating avian, gliadin, and reticulin antibodies suggested the diagnosis of gluten enteropathy, and jejunal biopsy showed subtotal villous atrophy. During 15 months on a gluten free diet his growth and behaviour improved and he required no transfusions.